Role of management accounting practices in creating values: A case study of Asia highway / Mohd Nur Hakim Bahaman and Ibrahim Kamal Abdul Rahman - Bahaman, Mohd Nur Hakim; Abdul Rahman, Ibrahim Kamal (2014)
Management accounting plays crucial role in a company because management accounting information helps managers to make decision. One of the areas that need critical analysis to make decision is marketing area where customers’ satisfaction is essential. In order to sustain customer satisfaction, various efforts need to be done by a company so that values to customer can be delivered. This study examined the role played by management accounting practices in the biggest highway concessionaires in the country in delivering values to customers. Furthermore, continuous improvement and innovation initiatives implemented by the company in delivering the customer values are carefully examined to see the how management accounting practices being applied in those initiatives. The impact of the efforts conducted, fi nancially and non-fi nancially were examined too.